Upaya Guru dalam Mengembangkan Kompetensi Sosial-Emosional Siswa Sekolah Dasar - Setyowati, Afra Hashnun; Abduh, Muhammad (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study is motivated by the importance of strengthening elementary school students’ social-emotional competencies as a foundation for character development and learning readiness. The objective of this study is to analyze teachers’ efforts in developing the social-emotional aspects of fourth-grade students at SDIT Nur Hidayah Surakarta. This research employs a descriptive qualitative approach, with data collected through observations and interviews using observation and interview guidelines as instruments. Data analysis is conducted interactively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that teachers play a strategic role in developing various social-emotional aspects of students, including self-awareness, self-confidence, self-adjustment, social interaction and communication, responsible decision-making, stress management, self-discipline, empathy, and self-regulation. These efforts are implemented through personal approaches, role modeling, providing motivation, instilling the value of trustworthiness (amanah), and habituating Islamic manners (adab). The results of this study confirm that the integration of a humanistic approach and character values in pedagogical practices is effective in supporting students’ holistic social-emotional development.